Becoming a woman of letters: myths of authorship and facts of the Victorian market - Peterson, Linda H. (Princeton Univ. Press, 2009)
Introduction: the 19th-century profession of letters and the woman author -- Inventing the woman of letters: Harriet Martineau in the literary -- Marketplace of the 1820's and 30's -- Working collaboratively: Mary Howitt and Anna Mary Howitt as women of letters -- Parallel currents: the life of Charlotte Bronte as mid-victorian -- Myth of women's authorship -- Challenging Brontean myths of authorship: Charlotte Riddell and a struggle for fame (1883) -- Transforming the poet: Alice Meynell as fin-de-siecle -- Englishwoman of letters -- The woman of letters and the new woman: reinventing Mary Cholmondeley